Brønsted Acid/Lewis Acid Cooperatively Catalyzed Addition of Diazoesters to 2H‐Chromene Acetals. Issue 31 (25th September 2014) - Luan, Yi; Qi, Yue; Gao, Hongyi; Ma, Qianqian; Schaus, Scott E.
Abstract: A Brønsted acid/Lewis acid dual catalyst system was developed to promote efficient C–C bond formation between a range of oxocarbenium precursors derived from chromene acetals and ethyl diazoacetate. The reaction proceeds under mild conditions and is tolerant of functionalized 2 H ‐chromenes and isochromene acetals. In addition, an asymmetric variant of diazoacetate addition towards 2 H ‐chromene acetals is described. Continued investigations include further optimization of asymmetric induction towards the formation of diazo ester substituted 2 H ‐chromene. Abstract : A Brønsted acid/Lewis acid dual catalyst system is developed to promote efficient C–C bond formation between oxocarbenium precursors derived from chromene acetals and ethyl diazoacetate. The reaction proceeds under mild conditions and is tolerant of functionalized 2 H ‐chromenes and isochromene acetals. An asymmetric variant of diazoacetate addition towards 2 H ‐chromene acetals is also described.